2018
DOI: 10.1186/s13052-018-0514-9
|View full text |Cite
|
Sign up to set email alerts
|

The first case of neonatal priapism during hypothermia for hypoxic-ischemic encephalopathy and a literature review

Abstract: Neonatal priapism is a rare condition with only 26 described cases in literature since 1879. It is defined as a persistent penile erection occurring in the first 28 days of life, lasting at least 4 h that usually happens in the first days (from 2 to 12 days). It is a very different condition compared to the adult one because in newborns it is a relatively benign phenomenon. As a result of this paucity of described cases, classification and management are not well known by most of neonatologists and currently t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Newborn males commonly have erections which were triggered by a distended urinary bladder, tactile stimulation, diaper changing, bathing and urethral catheterization. 1 These erections quickly subsided following withdrawal of the precipitating factor. These physiological erections also occured spontaneously and demonstrated that the nerves to penis were normal.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Newborn males commonly have erections which were triggered by a distended urinary bladder, tactile stimulation, diaper changing, bathing and urethral catheterization. 1 These erections quickly subsided following withdrawal of the precipitating factor. These physiological erections also occured spontaneously and demonstrated that the nerves to penis were normal.…”
Section: Discussionmentioning
confidence: 99%
“…7 Available literature on this pathology was limited to less than 30 case reports. 1 These reports were spread across the various continents including one in Asia. Sood et al reported a case of neonatal priapism in India in 2006.…”
Section: Figure 1: (A and B) Shows The Priapsim Experiencedmentioning
confidence: 99%
See 3 more Smart Citations